PMB Pembaruan Aplikasi Pendaftaran Mahasiswa Baru Stmik Bandung Menggunakan Siklus SPA (Single Page Application) - Linda Apriyanti; Mina Ismu Rahayu; Ade Winarni (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
Along with the advancement of information and communication technology, particularly internet and web technologies, STMIK Bandung has implemented an Information System for New Student Admissions (PMB). Although this system has provided various benefits, the lack of separation between the Front-End and Back-End code structures in the current PMB application has led to limitations in scalability and performance optimization. When traffic increases, it becomes difficult to scale the Back-End infrastructure without affecting Front-End performance. As a solution, the development of a PMB system based on the Single Page Application (SPA) architecture is proposed. SPA enables a website to load only the necessary components based on user interactions instead of reloading the entire page, significantly improving speed and responsiveness. The software development methodology used in this project is Agile. By implementing SPA, STMIK Bandung can optimize user experience, enhance system stability, and simplify the software development and maintenance process. The research results show that the implementation of SPA not only modernizes the PMB system but also increases efficiency and convenience for users.